Floating knee injuries - An Analysis of Outcome in Surgically Treated Patients in a Tertiary Care Institution - Ezhilmaran Radhakrishnan; Maharajothi Paramasivam; Narayanan AR (Journal of the Bulgarian Orthopaedics and Trauma Association, 2023)
Background: Floating knee injuries are not uncommon and they occur due to high velocity trauma and are usually associated with other injuries. Early intervention in the form of internal fixation of both the femur and tibia usually results in better functional outcome. The present study was conducted with an aim to analyze the factors influencing the functional outcome of patients with ipsilateral femur and tibia fractures using Karlstrom and Olerud’s criteria.